Future Directions for Mapping Atrial Fibrillation - Junaid AB Zaman; Andrew A Grace; Sanjiv M Narayan (Arrhythmia & Electrophysiology Review)
Mapping for AF focuses on the identification of regions of interest that may guide management and – in particular – ablation therapy. Mapping may point to specific mechanisms associated with localised scar or fibrosis, or electrical features, such as localised repetitive, rotational or focal activation. In patients in whom AF is caused by disorganised waves with no spatial predilection, as proposed in the multiwavelet theory for AF, mapping would be of less benefit. The role of AF mapping is controversial at the current time in view of the debate over the underlying mechanisms. However, recent clinical expansions of mapping technologies confirm the importance of understanding the state of the art, including limitations of current approaches and potential areas of future development.